2018
DOI: 10.1186/s41043-017-0132-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adherence to tuberculosis treatment in Asmara, Eritrea: a qualitative study

Abstract: BackgroundNon-adherence to tuberculosis (TB) treatment is an important barrier for TB prevention and control. Poor adherence may result in prolonged disease infectiousness, drug resistance, relapse and death. The aim of this study was to assess factors influencing adherence to tuberculosis treatment in selected health facilities in Asmara, Eritrea.MethodsA qualitative study which included in-depth interviews with 12 TB patients, three focus group discussions in selected health facilities in which one group com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
102
1
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(156 citation statements)
references
References 18 publications
15
102
1
20
Order By: Relevance
“…Consequently, people fear to get infected with TB, which is the most common cause of TB stigma. (22)(23)(24)(25) Our study showed that LTBI related stigma is, to a great extent, comparable to TB related stigma. This is in line with a previous study among Chinese immigrants in Canada, which linked LTBI related stigma to limited knowledge about LTBI and confusion with TB disease.…”
Section: Participant On Ltbi Treatment: "When Some Friends Offer Yousupporting
confidence: 57%
“…Consequently, people fear to get infected with TB, which is the most common cause of TB stigma. (22)(23)(24)(25) Our study showed that LTBI related stigma is, to a great extent, comparable to TB related stigma. This is in line with a previous study among Chinese immigrants in Canada, which linked LTBI related stigma to limited knowledge about LTBI and confusion with TB disease.…”
Section: Participant On Ltbi Treatment: "When Some Friends Offer Yousupporting
confidence: 57%
“…The lack of knowledge about the transmission routes of TB also contributes to stigma. The lack of a comprehensive understanding of the barriers and facilitators of treatment adherence is also an obstacle in finding effective solutions to manage TB (Gebreweld et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finding ways to make our patients understand their disease and the therapeutic implications is not an easy task, especially when cultural factors, like a patriarchal physician-patient relation, limited interactions [14]. In our study, adherence was only partially influenced by the disease comprehension, while others found that knowledge stood out as a significant factor that influences adherence [15, 16]. …”
Section: Discussionmentioning
confidence: 63%